Nekara: Peninggalan Seni Budaya dari Zaman Perunggu - Hanny Wijaya (Humaniora, 2013)
Cultural development nowadays could not be separated with the cultural development from the past. Dong Son culture, which was developed in Vietnam area, had given a big influence to cultural development in Asian regions during the Bronze Age. One of the great heritages from Dong Son culture was a Dong Son drum or was known as Nekara in Indonesian region. Nekara which forms like a drum has many functions that based on culture and tradition from each area. The main function of Nekara was generally as a music instrument for festivals or cultural events, such as prayers for rain, good harvest, funeral, wedding ceremony, etc. Moreover, in some specific regions, nekara had also been used as a mausoleum to keep the corpse or dead body for funeral, it was also had a function as a symbol of power for tribe leaders. The motifs on drums or nekara also had a symbolic meaning or a specific representation based on its function.Article presents the knowledge on  the background and function of nekara more specific and readers will know more details about Dong Son culture and its unique heritage, i.e. Nekara.